Analysis of the Influence of Digital Marketing and Consumer Trust on Shopee Purchase Decisions in Medan City - Irvan Rolyesh Situmorang; Steven Andrean; Jessy Jessy; Edbert Tanoto; Winsen Winsen; Jimmy Jimmy; Marco Tianov (SEAN Institute, 2026)
This study aims to analyze the influence of Digital Marketing and Consumer Trust on Purchase Decisions of Shopee users in Medan City. The development of information technology has shifted public consumption patterns to digital-based, requiring e-commerce platforms to optimize marketing strategies and build credibility. The research method used is causal associative quantitative with a sample of 100 respondents selected through non-probability sampling techniques in the Medan City area. The data analysis technique used multiple linear regression with the help of statistical software. The results showed that partially, Digital Marketing has a positive and significant effect on Purchase Decisions. Likewise, Consumer Trust is proven to have a positive and significant influence on Purchase Decisions. Simultaneously, both independent variables significantly influence Purchase Decisions with a coefficient of determination (R²) value of 68%. These results indicate that the integration between interactive digital marketing strategies and a secure platform reputation is a key factor in driving consumer transactions in the Medan digital market.